Perspectives in a pandemic - Cahill, Kevin M. (International Humanitarian Affairs, 2020)
Perspectives in a Pandemic is a series of enlightening essays written by Kevin M. Cahill, M.D., providing a unique insight into the early phase of the COVID-19 pandemic. Dr. Cahill draws on his extensive experiences in earlier epidemics, natural disasters, and armed conflicts to offer lessons, wisdom, guidance and support to frontline workers. While he wrote the essays as weekly reflections in the early months of the pandemic for the thousands of humanitarian relief workers he has trained around the world, this book is a must read for anyone seeking to understand, and make some sense of, the complexities and chaos inevitable in a pandemic.